Strategies to Boost Boiler Efficiency and Reduce Operational Downtime: Strategi untuk Meningkatkan Efisiensi Boiler dan Mengurangi Waktu Henti Operasional - Fakhrizi, Rendy Rakhmad; Mulyadi, Mulyadi (Universitas Muhammadiyah Sidoarjo, 2024)
This study examines the decline in boiler performance, highlighting the imperative of efficient maintenance to prevent operational disruptions and financial losses. The focus is on the analysis of boiler functionality, identifying factors that contribute to reduced efficiency and increased downtime. Utilizing performance data from August 2023, the research documents a significant downtime of 4610 minutes, primarily attributed to mechanical issues and extended recovery periods totaling 1920 minutes. The study also reports a high fuel usage efficiency ratio of 35 Kg/cm3, underscoring the challenges in initial recovery efforts. Despite these setbacks, machine quality metrics indicated no defects, suggesting effective quality control measures. The findings underscore the critical relationship between maintenance strategies and boiler efficiency, proposing that proactive maintenance could mitigate downtime and enhance productivity, thereby supporting sustained operational efficiency. Highlights: Maintenance crucial for boiler efficiency and cost savings. Downtime leads to production delays and financial losses. Performance metrics indicate operational reliability and effectiveness. Keywords : Boiler, Maintenance, Operating Time